A Tripartite Evolutionary Game Approach to Rural E-Commerce Development under the Digital Economy: Mechanism and Policy Implications - Xin Li; Ning Zhang; Shi Yin (Journal of Innovative Research in Mathematical and Computational Sciences, 2024)
In the era of the digital economy, the high-quality development of rural e-commerce conforms to the trend of rural revitalization and urban-rural integration. As a link between small-scale farmers and the large market, rural e-commerce injects new impetus into the modernization of agriculture and rural areas by reconstructing the circulation system of agricultural products, activating rural resource elements, and cultivating new types of business subjects. Based on the dynamic game relationship among the three subjects of the government, e-commerce enterprises, and farmers, this paper constructs an evolutionary game model and conducts numerical simulations to explore the key factors influencing the coordinated development. The research findings are as follows: (1) The resource integration ability of e-commerce enterprises is positively correlated with the speed of system evolution, which can promote cooperation among the three subjects. (2) The government’s fiscal subsidies and incentive supervision policies play an important role in activating the coordination among the three subjects. (3) The awareness of new e-commerce models among farmers is an important factor in the current high-quality development of rural e-commerce, which has a significant effect on accelerating the cooperation among the three subjects. (4) By establishing a dynamic supervision system based on credit ratings and following a composite governance path of "policy guidance - technological empowerment - community co-governance", a dynamic balance can be maintained between market vitality and consumer rights. This study provides practical guidance for resolving the coordination dilemma in the rural e-commerce ecosystem.